2015
DOI: 10.1002/ajmg.a.37139
|View full text |Cite
|
Sign up to set email alerts
|

10 years later: Assessing the impact of public health efforts on the collection of family health history

Abstract: In 2004, a nationwide survey found that the majority (96.3%) of Americans believed their family health history (FHx) was important for their own health; however, only a third (29.8%) of respondents had ever actively collected this information. Over the past decade, government agencies, advocacy groups, professional societies, and healthcare provider organizations have aimed to improve the collection rates and utilization of FHx. This study assesses the current attitudes, knowledge, and practices of Americans r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 12 publications
2
30
0
Order By: Relevance
“…The general population appears to have high levels of family history knowledge of general health issues such as diabetes (Welch, O’Connell, & Schiffman, 2015), but this may not be the case for many Deaf individuals. Since most Deaf individuals have hearing family members, there is frequently a language barrier that results in a loss of family history awareness (Hauser, O’ Hearn, McKee, Steider, & Thew, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The general population appears to have high levels of family history knowledge of general health issues such as diabetes (Welch, O’Connell, & Schiffman, 2015), but this may not be the case for many Deaf individuals. Since most Deaf individuals have hearing family members, there is frequently a language barrier that results in a loss of family history awareness (Hauser, O’ Hearn, McKee, Steider, & Thew, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple USA national strategies initiated to improve individuals’ family history recording little change has occurred over a 10 year period; only 36.9% actively collecting it (Welch et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Family history is a very important assessment tool in detecting those at risk (Welch et al. ). We know that primary relatives have at least twice the risk of certain cancers; especially breast cancer (Colditz et al.…”
Section: Introductionmentioning
confidence: 99%
“…112 However, family history recording and assessment has been a weakness in the oncology community 123,124 challenges for family history collection include lack of time, lack of training, lack of accuracy, and lack of family history tools for clinicians and their patients. 125,126 In many clinical trials and genomic research studies, family history has been omitted or incompletely recorded and/or reported. This, along with de novo mutations and incomplete penetrance, presents barriers when interpreting family history as a risk factor for cancer predisposition.…”
Section: Implications Of Genomics For Patient Management: Clinical Camentioning
confidence: 99%